2021
DOI: 10.1177/0271678x21994395
|View full text |Cite
|
Sign up to set email alerts
|

Activation of astroglial CB1R mediates cerebral ischemic tolerance induced by electroacupuncture

Abstract: There are no effective treatments for stroke. The activation of endogenous protective mechanisms is a promising therapeutic approach, which evokes the intrinsic ability of the brain to protect itself. Accumulated evidence strongly suggests that electroacupuncture (EA) pretreatment induces rapid tolerance to cerebral ischemia. With regard to mechanisms underlying ischemic tolerance induced by EA, many molecules and signaling pathways are involved, such as the endocannabinoid system, although the exact mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…Recent research revealed that the neuroprotection provided by EA was associated with activation of the parasympathetic nervous system in experimental stroke model animals 31 . EA pretreatment also can increase ambient endocannabinoid levels and result in activation of the ischemic penumbral astroglial cannabinoid type 1 receptor, which led to moderate upregulation of extracellular glutamate that protected neurons from cerebral ischemic injury 32 . In addition, EA can promote the survival and synaptic plasticity of hippocampal neurons and improve spatial memory disorders caused by sleep deprivation 33 .…”
Section: Gv‐ea Promotes the Survival Of Injured Sc Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research revealed that the neuroprotection provided by EA was associated with activation of the parasympathetic nervous system in experimental stroke model animals 31 . EA pretreatment also can increase ambient endocannabinoid levels and result in activation of the ischemic penumbral astroglial cannabinoid type 1 receptor, which led to moderate upregulation of extracellular glutamate that protected neurons from cerebral ischemic injury 32 . In addition, EA can promote the survival and synaptic plasticity of hippocampal neurons and improve spatial memory disorders caused by sleep deprivation 33 .…”
Section: Gv‐ea Promotes the Survival Of Injured Sc Neuronsmentioning
confidence: 99%
“… 31 EA pretreatment also can increase ambient endocannabinoid levels and result in activation of the ischemic penumbral astroglial cannabinoid type 1 receptor, which led to moderate upregulation of extracellular glutamate that protected neurons from cerebral ischemic injury. 32 In addition, EA can promote the survival and synaptic plasticity of hippocampal neurons and improve spatial memory disorders caused by sleep deprivation. 33 Interestingly, a previous research suggested that EA protected cerebral hippocampal neurons in vascular dementia by inhibiting the expression of p53 (a tumor suppressor) and Noxa (p53 downstream effector) in hippocampal CA1 region.…”
Section: Gv‐ea Promotes the Survival Of Injured Sc Neuronsmentioning
confidence: 99%
“…The cell-type-specific expression of CB1R in lumbar spinal cord dorsal horn Note: In each segment of lumbar spinal cord, four to six sections were counted from each male (n = 3) and female (n = 4) mice to characterize the CB 1 R expression in the GABAergic, glycinergic, and glutamatergic neurons in the dorsal horn. These data are the collection from Figure 6 demonstrated that low-level expression of CB 1 Rs is detectable in astrocytes in several brain areas (Gutierrez-Rodriguez et al, 2018;Han et al, 2012;Rodriguez et al, 2001;Yang et al, 2021;Zhang et al, 2014), as well as in cultured microglial cells (Walter et al, 2003). However, the expression and sexual characteristics of CB 1 Rs in spinal glial cells are rarely reported.…”
Section: Ta B L Ementioning
confidence: 67%
“…EA also activates the dorsal motor nucleus of the vagus, the largest source of parasympathetic preganglionic neurons in the lower brainstem (detected by c-fos immunohistochemistry), and PD suppresses these changes [ 45 ]. EA pretreatment results in increased ambient endocannabinoid (eCB) levels and subsequent activation of ischaemic penumbral astroglial cannabinoid type 1 receptors (CB1Rs), which leads to moderate upregulation of extracellular glutamate that protects neurons from cerebral ischaemic injury [ 46 ].…”
Section: Resultsmentioning
confidence: 99%